Geometric based apple suction strategy for robotic packaging - Wang, Zhong; Wang, Qingyu; Lou, Mingzhao; Wu, Fan; Zhu, Yaonan; Hu, Dong; Zhou, Mingchuan; Ying, Yibin (International Journal of Agricultural and Biological Engineering, 2024)
Packaging is one of the least automated steps among all the fruit postharvest processes, which is time-consuming and labor-intensive. Therefore, a robust suction strategy for robotic manipulation needs to be developed. In this research, a geometric-based apple suction strategy for robotic packaging was studied, including suction cup design, optimal suction region selection algorithm, and robot system integration. In the first place, on the basis of the geometric features of the spheroid fruit, the structure of the suction cups was designed to provide reliable suction force. Then, suction force measurement experiments on both acrylic balls and apples were conducted. Based on the results, the parameters of the suction cup were finally determined. The results also indicated that the curvature radius of the suction region is supposed to larger than that of the suction cups. Furthermore, a robust suction region selection algorithm was developed, which involves four steps: RGB-D information acquisition, object detection and point cloud generation, spherical fitting, and suction region selection. Finally, the above methods were integrated into a robotic packaging system. In addition, on the basis of spatial-frequency domain imaging (SFDI) technology, early stage bruise was detected for validation. The results showed that, the proposed suction strategy and system is potential for robust robotic apple packaging.Keywords: apple, suction cup, robotic packaging, robotic manipulation, point cloudDOI: 10.25165/j.ijabe.20241703.7947Citation: Wang Z, Wang Q Y, Lou M Z, Wu F, Zhu Y N, Hu D, et al. Geometric based apple suction strategy for robotic packaging. Int J Agric & Biol Eng, 2024; 17(3): 12-20.